Characterization and Expression Pattern Analysis of the T-Complex Protein-1 Zeta Subunit in Musca domestica L (Diptera). Issue 4 (14th July 2017) - Zhao, Xuejun; Xiu, Jiangfan; Li, Yan; Ma, Huiling; Wu, Jianwei; Wang, Bo; Guo, Guo
Abstract: Chaperonins, belonging to the T-complex protein-1 (TCP-1) family, assist in the correct folding of nascent and misfolded proteins. It is well-known that in mammals, the zeta subunit of the TCP-1 complex (TCP-1ζ) plays a vital role in the folding and assembly of cytoskeleta proteins. This study reported for the first time the cloning, characterization and expression pattern analysis of the TCP-1ζ from Musca domestica, which was named as MdTCP-1ζ. The MdTCP-1ζ cDNA is 1, 803 bp long with a 1, 596 bp open reading frame that encodes a protein with 531 bp amino acids. The analysis of the transcriptional profile of MdTCP-1ζ using qRT-PCR revealed relatively high expression in the salivary glands and trachea at the tissues while among the developmental stages. The highest expression was observed only in the eggs suggesting that the MdTCP-1ζ may play a role in embryonic development. The expression of MdTCP-1ζ was also significantly induced after exposure to short-term heat shock and infection by Escherichia coli, Staphylococcus aureus, or Candida albicans . This suggested that MdTCP-1ζ may take part in the immune responses of housefly and perhaps contribute to the protection against cellular injury.